Deformation behavior of designed dual-phase CuZr metallic glasses. (15th April 2019) - Peng, C.X.; Şopu, D.; Cheng, Y.; Song, K.K.; Wang, S.H.; Eckert, J.; Wang, L.
Abstract: A nanometer-scale second phase in metallic glass (MG) heterostructures is effective to improve mechanical properties. In this work, molecular dynamics simulations are conducted to investigate the influence of various critical structural aspects such as the size/volume fraction, distribution of a nanoscale secondary phase and different combinations of the matrix and the secondary phase on the deformation behavior of dual-phase MGs. We find an obvious change in deformation mode with varying the size/fraction and the chemical composition of the secondary phase. When the yield stress of the dual-phase MGs is lower than critical shear stresses required for forming a mature shear band (SB), the MGs show homogeneous deformation. Otherwise, those dual-phase MGs with inclusions smaller than width of the SB or that cannot confine plastic zones between the larger inclusions have high tendency for shear instability and brittle failure. By systematically varying the characteristics of the secondary phase one can design MGs with improved mechanical properties. Graphical abstract: Unlabelled Image Highlights: Deformation mode obviously changes with varying the size/volume fraction and chemical composition of secondary phase. The heterostructures deform homogeneously when yield stress is lower than that required for forming a mature shear band. Homogeneous deformation occurs when plastic zones are confined between the large enough 'hard' inclusions.